Prevention of cisplatin nephrotoxicity - Hayati Fatemeh; Hossainzadeh Mehran; Shayanpour Shokouh; Abedi-Gheshlaghi Zahra; Beladi Mousavi Seyed Seifollah (Society of Diabetic Nephropathy Prevention, 2016)
Cisplatin has a well-established role in the treatment of broad spectrum of malignancies; however its use is limited because of cisplatin-induced nephrotoxicity (CIN) which can be progressive in more than 50% of cases. The most important risk factors for CIN include higher doses of cisplatin, previous cisplatin chemotherapy, underlying kidney damage and concurrent treatment with other potential nephrotoxin agents, such as aminoglycosides, nonsteroidal anti-inflammatory agents, or iodinated contrast media. Different strategies have been offered to diminish or prevent nephrotoxicity of cisplatin. The standard approach for prevention of CIN is the administration of lower doses of cisplatin in combination with full intravenous hydration prior and after cisplatin administration. Cisplatin-induced oxidative stress in the kidney may be prevented by natural antioxidant compounds. The results of this review show that many strategies for prevention of CIN exist, however, attention to the administration of these agent for CIN is necessary.